18+4(p-9)=36

Simple and best practice solution for 18+4(p-9)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18+4(p-9)=36 equation:


Simplifying
18 + 4(p + -9) = 36

Reorder the terms:
18 + 4(-9 + p) = 36
18 + (-9 * 4 + p * 4) = 36
18 + (-36 + 4p) = 36

Combine like terms: 18 + -36 = -18
-18 + 4p = 36

Solving
-18 + 4p = 36

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 4p = 36 + 18

Combine like terms: -18 + 18 = 0
0 + 4p = 36 + 18
4p = 36 + 18

Combine like terms: 36 + 18 = 54
4p = 54

Divide each side by '4'.
p = 13.5

Simplifying
p = 13.5

See similar equations:

| 1.5x+6=-1.5x+12 | | 4+256x^3=0 | | 2v^2-5=-3v | | 49x^2-56x-159=0 | | s=0.164t-0.65 | | 3/7a=-5 | | 2v^2-5=0 | | 971-((4+788))x(470-454)= | | -d/4=-4.7 | | 2(9x+9)= | | 6r+7+5r+2r=19 | | -1.5z+7=1.5z+1 | | 2x^2-3xy+4y^2-3=0 | | 2n-13=39 | | X+1=6x+12 | | 7y-28=-19+6y | | 3x+10=9x-12 | | 9b-8-3b+5=21 | | 5s+8-4s= | | 971-4= | | 25n^4-9=0 | | -(8w+5)+3(w-15)= | | C^2+12c+36=0 | | 7y-28=-19+6 | | 6z-8z=-2z-24 | | 5-11w=7(5-2w) | | -8x+10=-25 | | 5.25x+6.5*4y=906.25 | | 2m^2*2m^2= | | 6x^4-x^2-5=0 | | 3(4v-8)=24+4v | | 5.2x-8=110.5 |

Equations solver categories